PEMBELAJARAN OPERASI HITUNG PECAHAN PADA SISWA SD KELAS VI DENGAN MENGGUNAKAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) - Alawiah, Willy (IKIP Siliwangi, 2021)
AbstractFractions are one of the most important materials in mathematics. If there is a problem understanding the concept of counting fractions, it is certain that our students experience misconceptions about fractions. Most of the learning processes used by teachers are conventional learning, namely lectures, question and answer and assignments. In this case, the learning process is dominated by the teacher. Therefore, the learning approach needs to be changed immediately. One of the current mathematics learning approaches that can be applied is Realistic Mathematics Education (RME). in RME students are encouraged or challenged to actively learn. This study aims to examine the scenario and implementation of learning operations for fraction counting for 6th grade elementary school students using the Realistic Mathematics Education (RME) approach, the responses of teachers and elementary school students in grade VI to learning operations for fraction counting using the Realistic Mathematics Education (RME) approach, and the difficulties difficulties experienced by grade VI elementary school students in completing fraction count operations tasks. The method used in this research is descriptive research with a qualitative approach. The descriptive method was chosen because the research carried out was related to ongoing events and with regard to current conditions. The results showed that the scenario and implementation of learning operations for fraction counting of grade VI elementary school students using the Realistic Mathematics Education (RME) approach included five steps / syntax that have become the hallmarks of learning, namely: using contextual problems, using models, using student contributions, interactivity, and the existence of linkages. The response of elementary school teachers and students of grade VI to learning operations to count fractions using the Realistic Mathematics Education (RME) approach on the aspect of clarity. The teacher strongly agrees to use the RME approach in learning fraction arithmetic operations, because students are more active and creative when learning takes place. In the aspect of student curiosity, the teacher is very happy to use the media of real objects because according to them learning is more interesting and can imagine with just one explanation. Student responses to learning fraction count operations using the RME approach they think are positive because learning using the RME approach makes learning easier. The difficulties experienced by grade VI elementary school students in completing fraction count operations tasks based on student questionnaires, namely students do not understand the content and purpose of the questions provided and there are students who sometimes forget mathematical rules, formulas and simplification of mathematical sentences or an equation. Keywords: Realistic Mathematics Education (RME), Fractions